O DESENVOLVIMENTO DE EVENTOS COMO ESTRATÉGIAS DA COMUNICAÇÃO ORGANIZACIONAL: UM ESTUDO DE CASO DA UNIVERSIDADE METODISTA DE SÃO PAULO - Pessoa, Mirella Arruda (2014)
Research on the events of the Universidade Metodista de São Paulo in search of verifying their efficiency in organizational goals and objectives. Based on the literature, we sought to understand organizations, relating to communications that they have with their audiences, among them: advertising, public relations, media relations, and especially events. Through the literature, it was established types of events and functions, and also realize that they function as strategic tools of organizational communication. The methodology consists of bibliographic and documentary research, and study of organizational cases. Questionnaires to the participant of public events were applied in two occasions: Dia da Universidade Aberta (facing the external public of the institution) and Aniversário do Instituto Metodista de Ensino Superior (facing the workforce of the University), both developed by UMESP. In addition, semi-structured interview was taken with the Communications Director of the Institution, establishing a relationship between what the public realized during events and what the University thought when decided to do these events.